Tests on the general instability of a stiffened metal cylinder under axial compression - Heald, W. R. (College of Aeronautics, Cranfield, 1951)
A thin stiffened metal cylinder liable to General Instability was tested under axial compression and an investigation was made into possible methods of predicting the critical load from non-destructive tests. Particular attention was paid to the perturbation loading technique. The cylinder was finally tested to destruction and the actual failing load compaired with the values given by various theories and empirical relationships.